Klebsiella pneumoniae liver abscess with purulent meningitis and endogenous endophthalmitis: A case report - Li, Fang; Zheng, Wenfei; Yu, Jian; Zhao, Linyan (Frontiers in Surgery, 2022)
This is a rare but typical case of Klebsiella pneumoniae liver abscess with migratory infections including purulent meningitis and endogenous endophthalmitis. The patient had a chief complaint of 7 days of fever, 4 days of blurry vision and 4 hours of glossolalia. Ultrasound scan and computed tomography (CT) suggested a liver abscess. Blood and drainaged fluid cultures both grew Klebsiella pneumoniae with a high mucosal phenotype. The patient was finally diagnosed with Klebsiella pneumoniae liver abscess, purulent meningitis and endogenous Klebsiella pneumoniae endophthalmitis in right eye. Ultrasound-guided percutaneous catheter drainage (PCD) of the liver abscess was performed and meropenem was used to control infection. Vancomycin (10g/L) 0.1mL and ceftazidime (20g/L) 0.1mL was given by intravitreal injection for a treatment of endophthalmitis. The infection was gradually controlled after such treatments. The patient was discharged from our hospital with a better condition. During the time of follow-up, she was eventually died of complications of severe pneumonia in local hospital.This case revealed that a rapid diagnosis followed by appropriate treatment would improve the prognosis and prevent severe metastatic complications.